Mechanistic insights into enhanced waste activated sludge dewaterability with Cu(II) and Cu(II)/H2O2 treatment: Radical and non-radical pathway. (February 2022) - Liu, Xiaoping; Zhai, Yunbo; Liu, Guangli; Liu, Xiangmin; Wang, Bei; Wang, Zhexian; Zhu, Ya; Fan, Yuwei; Shi, Haoran; Xu, Min
Abstract: Without extra adjustment of pH, the effects of cupric ions (Cu(II)) and hydrogen peroxide (H2 O2 ) alone or in combination on sludge dewatering were studied. It showed good dewatering capability after treated by Cu(II) and Cu(II)/H2 O2, which indicated by the capillary suction times (CST) decreased from 120.8 ± 4.7 s (control) to about 40 s, and the water content (Wc) of sludge cake dropped by about 10%. The results showed that the extracellular polymeric substances (EPS) were destroyed, which characterized by a significant decrease in the biopolymers' concentrations in tightly-bound EPS. Meanwhile, more rough and porous microstructures and higher zeta potentials were obtained after conditioned. Based on the changes of physicochemical properties of sludge, the variations of EPS, and the identification of reactive species, two distinct mechanisms of improved sludge dewatering were postulated. As for Cu(II) treatment, it was mainly due to the surface charge neutralization, strong cytotoxicity of Cu(I) produced by intracellular reduction of Cu(II), and pH decline caused by Cu(II) hydrolysis that improved sludge dewatering performance, which could be noted as a "non-radical pathway". When in combination with H2 O2, hydroxyl radicals (·OH) produced by Cu(II)-catalyzed Fenton-like process played a dominant role in degrading sludge flocs and EPS, which could be regarded as a "radical pathway". Graphical abstract: Image 1 Highlights: Both Cu(II) and Cu(II)/H2 O2 treatment can improve dewaterability of sludge. The two processes resulted in CST reduction of about 69%. Cu(I) facilitated sludge dewatering in the Cu(II) treatment. Hydroxyl radicals play a major role in sludge dewatering by Cu(II)/H2 O2 process.